2019
DOI: 10.1016/j.jtho.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Non-Comparative Phase II Study of Anti-Programmed Cell Death-Ligand 1 Atezolizumab or Chemotherapy as Second-Line Therapy in Patients With Small Cell Lung Cancer: Results From the IFCT-1603 Trial

Abstract: Introduction: This randomized phase II trial aimed at evaluating the engineered programmed cell death ligand 1 (PD-L1) antibody atezolizumab in SCLC progressing after first-line platinum-etoposide chemotherapy. Methods: Patients were randomized 2:1 to atezolizumab (1200 mg intravenously every 3 weeks) until progression or unacceptable toxicity, or conventional chemotherapy (up to 6 cycles of topotecan or re-induction of initial chemotherapy). Patients were not selected based on PD-L1 tissue expression. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 18 publications
4
131
1
4
Order By: Relevance
“…Overall, 64% of the patients had platinum-sensitive disease (defined as disease progression ≥90 days after completion of induction chemotherapy). Results from this trial, published in January 2019, revealed no significant difference in median OS (9.5 months versus 8.7 months; HR 0.84, 95% CI 0.45-1.58; P = 0.60) 45 . Furthermore, median PFS was statistically inferior in patients who received atezolizumab (1.4 months versus 4.3 months in patients receiving chemotherapy; adjusted HR 2.26, 95% CI 1.3-3.9; P = 0.004).…”
Section: Second-line or Later Monotherapymentioning
confidence: 79%
“…Overall, 64% of the patients had platinum-sensitive disease (defined as disease progression ≥90 days after completion of induction chemotherapy). Results from this trial, published in January 2019, revealed no significant difference in median OS (9.5 months versus 8.7 months; HR 0.84, 95% CI 0.45-1.58; P = 0.60) 45 . Furthermore, median PFS was statistically inferior in patients who received atezolizumab (1.4 months versus 4.3 months in patients receiving chemotherapy; adjusted HR 2.26, 95% CI 1.3-3.9; P = 0.004).…”
Section: Second-line or Later Monotherapymentioning
confidence: 79%
“…In addition, ∼65% of new patients are at an extensive stage when diagnosed, and <5% of those patients survive for 2 years (23,24). Several ongoing phase I, II, and III clinical trials have revealed the primary results of PD-1 inhibitors for SCLC (25,26). In the present meta-analysis, nine relevant studies were included to explore the prognostic impact of PD-L1 expression on SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The additive effect of atezolizumab in the current case is better understood, as CE readministration immediately before the current treatment resulted in PD. Atezolizumab monotherapy in patients treated with first‐line platinum‐etoposide chemotherapy has previously demonstrated efficacy (IFCT‐1603 trial), in which the response rate and median PFS were 2.3% and 1.4 months, respectively 8 . Although the IFCT‐1603 trial resulted in a negative result, Kaplan‐Meier estimates of both PFS and OS in the atezolizumab group exhibited a tail plateau, suggesting that there is a selected population who may benefit from SCLC second‐line atezolizumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%